Solar thermal organic Rankine cycle as a renewable energy option - Cheng, Eng Cong; Velautham, Sanjayan; Darus, Amer Nordin (Faculty of Mechanical Engineering, 2005)
collector are sized according to the solar flux distribution in Malaysia. According to Malaysia Metrological Department, Kota Kinabalu has the highest yearly average of solar radiation in the country for year 2003, for this reason it is chosen for the location of study. The power generation system consists of two cycles, the solar thermal cycle that harness solar energy and the power cycle, which is the ORC that generates electricity. The solar thermal cycle circulates heat transfer fluid (HTF) in the cycle and harness thermal energy from the sun and transfers it to the organic compound in the ORC via a heat exchanger. Components in the power cycle or ORC include an ORC turbine for power generation, a condenser for heat rejection, a pump to increase the pressure and a heat exchanger. The HTF selected in this analysis is Therminol VP3, which is currently used for commercial solar thermal applications. For this research, 2 organic compounds were analyzed, R123 and isobutane. These two compounds are optimized for selection.